Not everything is blue or brown: Quantification of ocular coloration in psychological research beyond dichotomous categorizations - Perea García, Juan Olvido; Grenzner, Tomáš; Hešková, Gabriela; Mitkidis, Panagiotis (Communicative & integrative biology, 2017)
The notion that phenomenologically observable differences in the human eye are correlated with behavioral tendencies (other than gaze-following) has been addressed poorly in the psychological literature. Most notably, the proposed correlations are based on an arbitrary categorization in discrete categories of the continuous variability across various traits that could be contributing to individual eye morphologies. We review the relevant literature and assume a view of human eyes as sign stimuli, identifying the relative contrast between the iridal and scleral areas as the main contributor to the strength of the signal. Based on this view, we present a new method for the precise quantification of the relative luminosity of the iris (RLI) and briefly discuss its potential applications in psychological research.
Keywords: eyes; color; sign stimulus; iris; variable control; methods